Deskripsi Kemampuan Motorik Kasar Anak Usia 5-6 - Rapi Us. Djuko; Sri Wahyuningsi Laiya; Amina Datu (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
This research method is qualitative research. Data collection techniques are carried out by observation, interviews and document studies. The source of the data is the description of gross motor abilities in group B. The data were analyzed qualitatively. Gross motor skills in children are divided into three, namely: locomotor, non-locomotor, and manipulative. The results showed that the child's locomotor ability can be seen from the way the child is able to make movements with body strength. Non-locomotor movements can be seen from the way children are able to make movements with agility, namely children are able to move quickly, and manipulative movements can be seen from the way children are able to make movements with balance, namely a child is able to choose and maintain his body position. The teacher teaches children to do and continues to teach children who have not been able to do the activities given by the teacher. From the results of the study, it was concluded that the description of gross motor skills, namely locomotor, non-locomotor and manipulative in children aged 5-6 years in Mutiara Laut Kindergarten, Oluhuta Village, Kabila Bone District, Bone Bolango Regency, was maximized